Genome-wide association study of myrtle rust (Austropuccinia psidii) resistance in Eucalyptus obliqua (subgenus Eucalyptus) - Thau, Wilson Lym Yong; Peter K. Ades; Fatima Akter Runa; Gerd Bossinger; Karanjeet S. Sandhu; Brad M. Potts; Josquin F.G. Tibbits (Springer, 2021)
Myrtle rust (caused by Austropuccinia psidii Beenken) is exotic to Australia, yet specific resistance is present in a range of naïve myrtaceous host plants. Resistance to myrtle rust is primarily quantitative in nature and controlled by multiple interacting loci. We undertook a genome-wide association study (GWAS) to discover relationships between nuclear genomic sequence variation and multiple aspects of resistance to A. psidii in Eucalyptus obliqua, a representative species from subgenus Eucalyptus. Sequence variation was assessed with respect to numeric severity, binary symptomatic, hypersensitive, and pustulation responses to inoculation of seedlings with A. psidii. A total of 1.13 million, single-nucleotide polymorphisms (SNPs) were tested for association with the rust resistance responses of 637 phenotyped E. obliqua seedlings, each from different, single mother tree seedlots. Thirty-three highly significant SNP-trait associations were detected, of which 26 associated with the binary symptomatic/asymptomatic response to A. psidii. Comparison of the genomic position of these SNPs with rust resistance loci (Ppr1-5), previously reported in species from subgenus Symphyomyrtus, suggested that several were positioned near the major Ppr1 locus and other Ppr loci. This study provides the first integrated genomic view of A. psidii resistance across the Eucalyptus subgenera and provides the foundation for discovering key resistance genes for use in marker-based resistance breeding.